Some lexical features of the French puzzles - Umirzakov Abdihamid Abdumominovich (Universitas Muhammadiyah Sidoarjo, 2019)
This paper investigates some lexical features of the french puzzles. On this case both theoritical and practical points were analysed and lexical investigation were mentioned. The way of French puzzles was discussed with methodolocial features as the whole. Finally, concluded different ideas were stated for the further development as the whole.